Impact of minimal residual disease on the outcome of hematopoietic stem cell transplantation for childhood acute lymphoblastic leukemia within the FORUM Trial - Adriana Balduzzi; Evgenia Glogova; Christina Peters; Petr Sedlacek; Jean-Hugues Dalle; Franco Locatelli; Roland Meisel; Birgit Burkhardt; Jochen Buechner; Jacek Wachowiak; Marc Bierings; Raquel Staciuk; et al. (Haematologica)
In the randomized cohort of the international phase-III FORUM trial, which showed the superiority of total-body irradiation (TBI) over chemotherapy-based conditioning prior to hematopoietic stem cell transplantation (HSCT) for pediatric acute lymphoblastic leukemia (ALL), type of conditioning and remission phase, but not pre-HSCT minimal residual disease (MRD), were associated with outcome. We report the impact of MRD within the extended FORUM cohort.